Addressable Organic Structure by Anisotropic Wetting. (21st February 2013) - Wang, Wenchong; Du, Chuan; Li, Liqiang; Wang, Hong; Wang, Chenguang; Wang, Yue; Fuchs, Harald; Chi, Lifeng
<x xml:space="preserve">Abstract</x> The anisotropic wetting of functional organic molecules on a patterned surface and the development of a photolithography‐compatible method to fabricate addressable organic structures is reported. For example, DtCDQA is grown on a SiO2 surface with a Au prepattern, achieving a high resolution cross‐over organic structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>